2020
DOI: 10.1111/jocs.14515
|View full text |Cite
|
Sign up to set email alerts
|

Repair of ischemic ventricular septal defect with and without coronary artery bypass grafting

Abstract: Background and Aim of the Study: Ventricular septal defect (VSD) following myocardial infarction (MI) is a relatively infrequent complication with high mortality.We sought to investigate the effect of concomitant coronary artery bypass graft (CABG) on outcomes following post-MI VSD repair.Methods: Electronic search was performed to identify all relevant studies published from 2000 to 2018. Sixty-seven studies were selected for the analysis comprising 2174 patients with post-MI VSD. Demographic information, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
4
9
1
Order By: Relevance
“…This meta-analysis shows that cCABG in surgery for post-AMI mechanical complications can be performed safely without significantly increasing early and late mortality, similarly to what Horan et al recently reported for VSR patients only (7). However, it should be noted that our analysis didn't consider percutaneous revascularization, that was carried out in 956 patients and is usually reported to improve survival (4,5).…”
Section: Elbadawi Et Al Recently Analyzedsupporting
confidence: 80%
See 3 more Smart Citations
“…This meta-analysis shows that cCABG in surgery for post-AMI mechanical complications can be performed safely without significantly increasing early and late mortality, similarly to what Horan et al recently reported for VSR patients only (7). However, it should be noted that our analysis didn't consider percutaneous revascularization, that was carried out in 956 patients and is usually reported to improve survival (4,5).…”
Section: Elbadawi Et Al Recently Analyzedsupporting
confidence: 80%
“…Cardiac rupture usually occurs in single-vessel disease (more frequently LAD) and during the first ischemic episode (24,31,39,47). In the current study, 54.3% of patients had single-vessel CAD (4,7,31). The role of lacking collateral circulation in its pathogenesis may also explain why 83.8% of PMR patients had posteromedial muscle rupture, being it more sensitive to ischemia, because it's usually supplied by terminal branches (58).…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…Overall, however, the majority of studies identified demonstrated no long-term survival benefit with concomitant CABG (25,26,28,33,48). This coincides with the findings of a recent systematic review on repair of postinfarction VSD with and without CABG, namely, that concomitant CABG did not have a significant effect on survival (49).…”
Section: Discussionsupporting
confidence: 84%